2012
DOI: 10.1152/ajplung.00288.2011
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-conditioned media recovers lung fibroblasts from cigarette smoke-induced damage

Abstract: Lee Y-S. Mesenchymal stem cell-conditioned media recovers lung fibroblasts from cigarette smoke-induced damage. Am J Physiol Lung Cell Mol Physiol 302: L891-L908, 2012. First published February 3, 2012 doi:10.1152/ajplung.00288.2011.-Cigarette smoking causes apoptotic death, senescence, and impairment of repair functions in lung fibroblasts, which maintain the integrity of alveolar structure by producing extracellular matrix (ECM) proteins. Therefore, recovery of lung fibroblasts from cigarette smoke-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 52 publications
(70 reference statements)
2
60
0
Order By: Relevance
“…For example, MSCs have proved to reverse apoptosis in cardiomyoblasts after ischemia, as well as damaged neurons and lung fibroblasts. 67, 68, 69 The anti-apoptotic mechanisms of MSCs are not fully understood, but several key proteins have been identified. IGF-1 and IL-6 secretion increases the expression of Akt (protein kinase B) and NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells).…”
Section: Identification and Biology Of Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MSCs have proved to reverse apoptosis in cardiomyoblasts after ischemia, as well as damaged neurons and lung fibroblasts. 67, 68, 69 The anti-apoptotic mechanisms of MSCs are not fully understood, but several key proteins have been identified. IGF-1 and IL-6 secretion increases the expression of Akt (protein kinase B) and NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells).…”
Section: Identification and Biology Of Mscsmentioning
confidence: 99%
“…132 MSC-conditioned media has been used to reverse cigarette smoke-induced damage in cultured lung fibroblasts; apoptotic death was inhibited, proliferation was increased and extracellular matrix synthesis was restored in response to MSC-conditioned media treatment. 69 Despite the promising basic science evidence and animal studies, human translation has yet to be optimized. In a 2012 double-blinded study of 62 COPD patients each subject received an infusion of 100 million allogeneic MSCs, resulting in significant reduction of circulating C-reactive protein.…”
Section: Clinical Translation Of Msc Therapiesmentioning
confidence: 99%
“…Aside from ALI, MSC-derived CM have also showed promising results in asthma[34] and chronic emphysema[35, 36], in terms of reducing inflammation and histological damage within the bronchoalveolar airspace and lung parenchyma. In both acute and chronic ovalbumin-induced asthma model in mice, Ionescu et al showed that MSC-derived CM attenuated inflammatory cells infiltrate into the alveolar space, restored the bronchodilator response to salbutamol, suppressed the increase in both dynamic lung resistance and elastance, and reduced airway smooth muscle layer thickening and peribronchial inflammatory infiltrate[34].…”
Section: Mesenchymal Stem Cells Secretome For Acute Lung Injury Anmentioning
confidence: 99%
“…While fibroblast contraction in collagen gels has been well characterized in models of skin and lung fibrosis [34,35], contraction of transdifferentiated esophageal epithelial cells in collagen matrices has not been previously described. Of the three tested cytokines, TNFα had the most significant effect upon collagen gel contraction, exceeding that of TGFβ.…”
Section: Discussionmentioning
confidence: 99%